Síntese do conhecimento científico sobre o extrativismo de recursos naturais - Ana Laura Biella Pereira (2021)
"Sustainability" is understood as the set of actions, processes and operations to achieve sustainable development. Such terms derive from the precaution and care in relation to natural resources, meeting the present human demands with future needs. The use of natural resources is associated with its extraction or provision form. So, to carry out the extractive activities in a sustainable way, it’s necessary a careful selection of the species or resources to be explored, field studies, monitoring the regeneration of the species/resource, calibration and improvement of extractivism through constant evaluation and academic development. Therefore, this dissertation shows a synthesis of scientific knowledge about the extraction of natural resources, in order to know the hot topics, trends of scientific research through scientometric analysis. In addition, to verify where these studies are distributed across the globe and perform a comparative analysis on the sources of bibliographic data. In order to investigate the scientific productions related to the extraction of natural resources, the bibliographic databases used to search for published documents were the ISI Web of Science - Main Collection (Clarivate Analytics) and SCOPUS (Elsevier). Bibliometric parameters were analyzed, such as ranking, frequency and distribution, having as study objects documents, magazines, articles, authors; and also scientometric aspects, such as set analysis and correspondence between themes, fields of research and communication between authors. The data analysis was performed with the EndNote 9 and Mendeley bibliography management softwares, the VosViewer software and the Microsoft Excel spreadsheet. The study highlights the importance of use different data bases to carry out a synthesis on scientific research on the extraction of natural resources, by the difference in the number of documents presented by the bases. We verify that there is cooperation for co-authoring scientific articles, but it was also found that cooperations are relatively recent, happening mostly since the 2000s, and is restricted to a main group of Asian authors. United States of America leads the ranking of publications in this subject. It was possible to identify demands and point directions to the scientific research development in the Neotropical regions and to the increase collaborations between scientists from the countries and institutions within this region. We verified a trend of conservation and sustainability focuses in the evaluated articles. The most cited articles with the highest number of links address topics of high global relevance and which have concentrated the attention of scientists, government officials and stack stakeholders, e.g., biofuels as an alternative to fossil fuels; extraction of natural resources and armed conflicts; influence of natural resources on a country's policy and development. So, there is a confluence in scientific approaches to extraction of natural resources related to sustainable practices and guidelines.